1986
DOI: 10.1128/aac.29.3.474
|View full text |Cite
|
Sign up to set email alerts
|

Effect of tobramycin on protein synthesis in 2-deoxystreptamine aminoglycoside-resistant clinical isolates of Haemophilus influenzae

Abstract: Clinical isolates of Haemophilus influenzae resistant to a broad range of 2-deoxystreptamine aminoglycosides (2-DAM) were studied. The gene responsible for resistance could be mobilized by transformation into a 2-DAM susceptible laboratory strain of H. influenzae, enabling isogenic comparisons. The transformants had the same resistance phenotype as the parental strains. There was close linkage between 2-DAM resistance and streptomycin resistance, a chromosomal marker, but weak linkage between 2-DAM and erythro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

1987
1987
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…Our results confirm that during exposure of E. coli to tobramycin, global macromolecular synthesis was eventually inhibited, as has been shown by several investigators (21,22,32,36). Gentamicin has been shown to bind to DNA in purulent material and lysed neutrophils (34 The precise mechanism of action of aminoglycoside-induced PAE remains a subject of speculation.…”
Section: Methodssupporting
confidence: 80%
“…Our results confirm that during exposure of E. coli to tobramycin, global macromolecular synthesis was eventually inhibited, as has been shown by several investigators (21,22,32,36). Gentamicin has been shown to bind to DNA in purulent material and lysed neutrophils (34 The precise mechanism of action of aminoglycoside-induced PAE remains a subject of speculation.…”
Section: Methodssupporting
confidence: 80%
“…Our third choice, tobramycin, an aminoglycoside, binds to bacterial ribosomal subunits and inhibits bacterial protein synthesis [41]. Nebulised tobramycin is also commonly used in the treatment of P. aeruginosa in CF patients, however in recent years, there has been a pattern of emerging resistance of CF bacteria against aminoglycoside antibiotics [42].…”
Section: Discussionmentioning
confidence: 99%
“…Tetracycline prevents the association of aminoacyl tRNA with the ribosome, which stops protein synthesis [13] and has no immediate effect on the cell membrane. We had previously shown that therapeutic tobramycin concentrations caused mistranslation in aminoglycoside susceptible H. influenzae [14]. …”
Section: Resultsmentioning
confidence: 99%